48.7k views
0 votes
Evaluate 3 + 1 1 t − 9 u 3+11t−9u3, plus, 11, t, minus, 9, u when t = 9 t=9t, equals, 9 and u = 1 1 u=11u, equals, 11.

User RKI
by
5.2k points

2 Answers

4 votes

Answer:

The correct answer is 3

Explanation:

Given the function

f(t, u) = 3 + 11t - 9u

To get the value of the function when t = 9 and u = 11, we will substitute the given variables into the given function to have;

f(9, 11) = 3 + 11(9) - 9(11)

f(9, 11) = 3 + 99 - 99

f(9, 11) = 3

User Manthan Dave
by
5.2k points
2 votes

We have to evaluate the value of the expression


3+11t-9u at t=9 and u=11

Consider the expression,


3+11t-9u

=
3+(11 * t)-(9 * u)

Substituting the given values, we get

=
3+(11 * 9)-(9 * 11)

=
3+99-99

= 3

So, the value of the given expression is 3.

User Rolnn
by
5.0k points